Scale, scope and impact of skill mix change in primary care in England: a mixed-methods study - Imelda McDermott; Sharon Spooner; Mhorag Goff; Jon Gibson; Elizabeth Dalgarno; Igor Francetic; Mark Hann; Damian Hodgson; Anne McBride; Katherine Checkland; Matt Sutton (Health and Social Care Delivery Research, 2022)
Background: General practices have had difficulty recruiting and retaining enough general practitioners to keep up with increasing demand for primary health care in recent years. Proposals to increase workforce capacity include a policy-driven strategy to employ additional numbers and a wider range of health professionals. Objectives: Our objective was to conduct a comprehensive study of the scale, scope and impact of changing patterns of practitioner employment in general practice in England. This included an analysis of employment trends, motivations behind employment decisions, staff and patient experiences, and how skill mix changes are associated with outcome measures and costs. Design: NHS Digital workforce data (2015–19) were used to analyse employment changes and to look at their association with outcomes data, such as the General Practitioner Patient Survey, General Practitioner Worklife Survey, prescribing data, Hospital Episode Statistics, Quality and Outcomes Framework and NHS payments to practices. A practice manager survey (August–December 2019) explored factors motivating general practices’ employment decisions. An in-depth case study of five general practices in England (August–December 2019) examined how a broader range of practitioners is experienced by practice staff and patients. Results: We found a 2.84% increase in reported full-time equivalent per 1000 patients across all practitioners during the study period. The full-time equivalent of general practitioner partners decreased, while the full-time equivalent of salaried general practitioners, advanced nurse practitioners, clinical pharmacists, physiotherapists, physician associates and paramedics increased. General practitioners and practice managers reported different motivating factors regarding skill mix employment. General practitioners saw skill mix employment as a strategy to cope with a general practitioner shortage, whereas managers prioritised potential cost-efficiencies. Case studies demonstrated the importance of matching patients’ problems with practitioners’ competencies and ensuring flexibility for practitioners to obtain advice when perfect matching was not achieved. Senior clinicians provided additional support and had supervisory and other responsibilities, and analysis of the General Practitioner Worklife Survey data suggested that general practitioners’ job satisfaction may not increase with skill mix changes. Patients lacked information about newer practitioners, but felt reassured by the accessibility of expert advice. However, General Practitioner Patient Survey data indicated that higher patient satisfaction was associated with a higher general practitioner full-time equivalent. Quality and Outcomes Framework achievement was higher when more practitioners were employed (i.e. full-time equivalent per 1000 patients). Higher clinical pharmacist full-time equivalents per 1000 patients were associated with higher quality and lower cost prescribing. Associations between skill mix and hospital activity were mixed. Our analysis of payments to practices and prescribing costs suggested that NHS expenditure may not decrease with increasing skill mix employment. Limitations: These findings may reflect turbulence during a period of rapid skill mix change in general practice. The current policy of employing staff through primary care networks is likely to accelerate workforce change and generate additional challenges. Conclusions: Skill mix implementation is challenging because of the inherent complexity of general practice caseloads; it is associated with a mix of positive and negative outcome measures. Future work: Findings from this study will inform future funding applications for projects that seek to examine the nature and impact of evolving multiprofessional teams in primary care. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 9. See the NIHR Journals Library website for further project information.